Tata Kelola Produksi Gula Semut Aren Berbasis Pemberdayaan Masyarakat: Studi Kasus di Desa Way Kalam Kabupaten Lampung Selatan - Ahmadi, Tyasto Prima; Putra, M. Reza Andrea; Bisri, Muawan; Wulansari, Wulansari; Sari, Yulia Puspita (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The production of palm sugar (gula semut aren) in Way Kalam Village is still carried out using traditional methods, characterized by limited technology, lack of quality standards, and weak institutional coordination. This study aims to analyze the governance of palm sugar production based on community empowerment through an interdisciplinary approach. The research employs a qualitative case study method, with data collected through field observations, semi-structured interviews with sugar producers, farmer groups, village officials, and the agricultural office, as well as analysis of supporting documents. The results reveal various inefficiencies in the production process, including bottlenecks during the drying phase, inconsistent product quality, and minimal adoption of appropriate technology. Using the Lean Production approach, wastes such as waiting time and overprocessing can be reduced by reorganizing workflow and optimizing equipment capacity. On the institutional side, strengthening farmer groups, enhancing inter-institutional coordination, and ensuring continuous mentoring are proven to be key factors in creating a more adaptive production ecosystem. This study recommends integrating technical and institutional strategies to sustainably empower palm sugar farmers. The proposed governance model can serve as a reference for developing a more efficient, competitive, and self-reliant village-based palm sugar industry.